1993
DOI: 10.1017/s0031182000067263
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between six species of Theileria using oligonucleotide probes which detect small subunit ribosomal RNA sequences

Abstract: SUMMARYThe complete small subunit ribosomal RNA (srRNA) gene of Theileria parva was cloned and sequenced. Two primers were designed which permitted the specific amplification of part of the Theileria srRNA gene from Theileria-infected cell line samples which were predominantly (> 95%) bovine DNA. The sequence of the central (variable) region of the srRNA genes of T. annulata, T. taurotragi, T. mutans and two unidentified parasites referred to as Theileria sp. (buffalo) and Theileria sp. (Marula) were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(88 citation statements)
references
References 29 publications
2
86
0
Order By: Relevance
“…This might explain the observation that free-ranging buffalo tested previously were 100% positive on IFAT for T. parva (Allsopp et al 1993). In addition, its close resemblance to T. parva in the 18S rRNA raised the question whether this was a variant strain of T. parva (Conrad et al 1987;Allsopp et al 1993). Subsequently, this parasite was detected in buffalo from the KNP that showed that T. sp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This might explain the observation that free-ranging buffalo tested previously were 100% positive on IFAT for T. parva (Allsopp et al 1993). In addition, its close resemblance to T. parva in the 18S rRNA raised the question whether this was a variant strain of T. parva (Conrad et al 1987;Allsopp et al 1993). Subsequently, this parasite was detected in buffalo from the KNP that showed that T. sp.…”
Section: Discussionmentioning
confidence: 95%
“…For this a 1101 bp fragment of the 18S rRNA gene for T. parva and T. sp. (buffalo) were amplified, respectively, using Theileria genus-specific primers 989 and 990 (Allsopp et al 1993), from cloned and sequenced products for T. parva and T. sp. (buffalo).…”
Section: Estimation Of Parasitaemia In Database Samplesmentioning
confidence: 99%
“…A 1101 bp fragment of the 18S rRNA gene was amplified using Theileria genus-specific primers designated as 989 and 990 by Allsopp et al (1993). Reaction conditions included the use of 25 μl GoTaq ® Green Ready reaction mix (Promega), 2·5 μl of DNA template and 10pmol of each primer up to a total volume of 50 μl.…”
Section: Cloning and Sequencing Of 18s Hyper-variable Regionmentioning
confidence: 99%
“…(buffalo) and T. sp. (bougasvlei) known to occur in buffalo and thought to be apathogenic (Allsopp et al 1993;Zweygarth et al 2008). Of these, T. parva was found in buffalo and cattle, while T. taurotragi was limited to cattle.…”
Section: The T Taurotragi Cladementioning
confidence: 99%
See 1 more Smart Citation